Room-Temperature Synthesis Of Bismuth Oxybromide-Based Photocatalysts For The Removal Of Ciprofloxacin From Aqueous Solution Under Visible Light - Imam, Saifullahi Shehu (2020)
Semiconductor photocatalysis using visible-light-driven photocatalysts is gaining more attention, due to its wide applications in energy conversion and environmental remediation. Recently, a ternary V-VI-VII semiconductor, bismuth oxybromide (BiOBr) has received extensive attention in photocatalysis due to its low cost, non-toxicity, and other unique properties. However, BiOBr alone exhibits low photodegradation efficiency, due to low visible light absorption and recombination of photogenerated charge carriers. Furthermore, for practical and large-scale application, the separation of powdered BiOBr is inconvenient. The primary aims of this work are to synthesize BiOBr-based photocatalysts at room-temperature, using facile, low cost and environmentally friendly methods, to enhance the photodegradation activity of BiOBr, as well as to ease the separation of the photocatalyst from the aqueous system. To achieve these goals, two strategies were employed. First, the pristine BiOBr was used as a host material to produce photocatalyst composites. Using this method, three BiOBr-based composites namely Bi/BiOBr, BiOBr/Bi2O3 and BiOBr/Bi2S3 were prepared. Second, the pristine BiOBr was immobilized onto cellulose acetate (CA), forming BiOBr/cellulose acetate (BCA) composite films. The structural and physicochemical properties of both powdered and immobilized BiOBr-composites were characterized using various techniques.